Answer:
(a) Because the expression is not an equation
(b) Because the expression is an equation
Explanation:
Solving (a): a + 2
The above expression can assume any value for a because it is not an equation.
Take for instance:
a = 2;
![a + 2 \to 2 + 2 = 4](https://img.qammunity.org/2022/formulas/mathematics/college/h3qcy7v5shxrj2w0iwn9mh42qlxz1cwi1m.png)
![a =-4](https://img.qammunity.org/2022/formulas/mathematics/college/39xubvvq3radpi6h9dtq7aisx3cakc6nh0.png)
![a + 2 \to -4 + 2 = -2](https://img.qammunity.org/2022/formulas/mathematics/college/7v2y6dpjlq8ufv4d1umsbhinwkakg2g23o.png)
The reason for this is because the expression is not an equation
Solving (b):
![b + 2 = 5](https://img.qammunity.org/2022/formulas/mathematics/college/84l7w1iiy4m2mw2pcrhb0h2w57aeptc6yh.png)
The above expression can assume only value for b, and the value is:
![b + 2 = 5](https://img.qammunity.org/2022/formulas/mathematics/college/84l7w1iiy4m2mw2pcrhb0h2w57aeptc6yh.png)
![b = 5-2](https://img.qammunity.org/2022/formulas/mathematics/college/6yukm3eyutb8f6olt8l340vvg5yqlvjohb.png)
![b =3](https://img.qammunity.org/2022/formulas/mathematics/college/j3l5aty4riz8pyyouq9h7g2pin5hmwt9il.png)
This means that only
will make the equation true.
The reason for this is because the expression is an equation